Breastfeeding during the COVID-19 pandemic - Chanda, Bwalya Mpelwa; Chen, Xiao-Qing (Frontiers in Pediatrics, 2023)
The coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused many significant changes to all aspects of day to day life. The disease has spread and reached pandemic proportions. The principle route of transmission is the respiratory route. Infants, pregnant women and breastfeeding mothers have all been affected. Many interventions and guidelines from important societies have been instituted in order to curb the transmission of the disease. These have involved both pharmacological and non-pharmacological methods. COVID-19 vaccines have also emerged as important methods of primary prevention of the disease. But several questions have been raised concerning the safety and efficacy of their use in pregnant and breastfeeding mothers. It has also not been clear if the vaccines are effective in generating a robust immune response in the pregnant women and breastfeeding mothers to confer passive immunity to the fetuses and infants, respectively. And they have not been tested in infants. The aspect of infant feeding has equally been affected. Although breast milk has not been known to serve as the vehicle of transmission of the virus, there is still some lack of uniformity of practice regarding breastfeeding when a mother has SARS-CoV-2 infection. This has led to infant feeding being done by the use of commercial formula feeds, pasteurized human donor breast milk, feeding on the mother's own expressed breast milk by a care giver and directly breastfeeding with skin to skin contact. This is despite breast milk being the most physiologically appropriate type of feed for infants. Therefore the pertinent question remains; should breastfeeding continue during the pandemic continue? This review also seeks to analyse the vast amount of scientific information regarding the subject and to synthesize science-based information